2013
DOI: 10.1002/asia.201300088
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Passivated SBA‐15‐Supported Gold Nanoparticles: Highly Improved Catalytic Activity and Selectivity toward Hydrophobic Substrates

Abstract: Silanol groups on a silica surface affect the activity of immobilized catalysts because they can influence the hydrophilicity/hydrophobicity, matter transfer, or even transition state in a catalytic reaction. Previously, these silanol groups have usually been passivated by using surface-passivation reagents, such as alkoxysilanes, bis-silylamine reagents, chlorosilanes, etc., and surface passivation has typically been found in mesoporous-silicas-supported molecular catalysts and heteroatomic catalysts. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…396 A major influence on the selectivity of catalytic sugar transformations is the prevalence of simultaneous side reactions (e.g., isomerization accompanying dehydration or hydrogenation at high reaction temperatures) and attendant deactivation of active sites and accumulation of insoluble side products (e.g., solid humins and residual organic species). Several strategies may offer improved selectivity: (i) passivation of catalyst supports for hydrogenation and oxidation to minimize the contribution of supports in reactions; 258,397,398 (ii) development of materials exposing preferred crystal facets, which have different adsorptive or catalytic capacities; 398−400 (iii) development of catalysts with tunable hydrophobicity to minimize water inhibition and favor interaction with organic reactants in water; 401,402 and (iv) control over acid site distributions to tune Brønsted:Lewis acid ratio and strength. 403,404 Advanced nanomaterials with hierarchical macro-mesoporous or meso-microporous architectures offer a means to improve mass transport as compared to microporous materials through superior in-pore accessibility.…”
Section: Future Catalyst Developmentmentioning
confidence: 99%
“…396 A major influence on the selectivity of catalytic sugar transformations is the prevalence of simultaneous side reactions (e.g., isomerization accompanying dehydration or hydrogenation at high reaction temperatures) and attendant deactivation of active sites and accumulation of insoluble side products (e.g., solid humins and residual organic species). Several strategies may offer improved selectivity: (i) passivation of catalyst supports for hydrogenation and oxidation to minimize the contribution of supports in reactions; 258,397,398 (ii) development of materials exposing preferred crystal facets, which have different adsorptive or catalytic capacities; 398−400 (iii) development of catalysts with tunable hydrophobicity to minimize water inhibition and favor interaction with organic reactants in water; 401,402 and (iv) control over acid site distributions to tune Brønsted:Lewis acid ratio and strength. 403,404 Advanced nanomaterials with hierarchical macro-mesoporous or meso-microporous architectures offer a means to improve mass transport as compared to microporous materials through superior in-pore accessibility.…”
Section: Future Catalyst Developmentmentioning
confidence: 99%
“…The importance of organic-inorganic hybrid silica-based materials in many fields of chemistry and relatedareas, such as electrochemistry, [1][2][3][4][5] catalysis, [6][7][8][9][10][11][12][13][14] separation, [12,15] adsorption, [16,17] CO 2 capture [16,18,19] and nanomedicine, [20][21][22][23][24] has steadily increasedi nr ecent years. Particular attention has been focused on ordered mesoporouss ilicas (OMSs), thanks to their intrinsic large surfaceareas, ordered and tuneable pore arrays with controlled size and huge available volume for hosting, reaction and release of molecules and ease of surfacef unctionalisation.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxidation reaction catalyzed by hydrophobic molecular sieve led to enhanced activity and selectivity. As an important class of heterogeneous catalysts, heterogeneous metal catalysts with metal nanoparticles dispersed and stabilized on high-surface supports have been widely applied in industry. Recently, many studies have successfully demonstrated that the hydrophobic modification on supports helps to enhance the catalysis of supported metal nanoparticles. The hydrophobic mesoporous polymeric shell endowed the Au@polymer nanostructure with the selective catalytic activity by selectively allowing hydrophobic molecules to pass through the shell to reach the catalytic Au sites . Superhydrophobic SBA-15-supported Au nanoparticles using surface passivation displayed much improved catalytic activity and selectivity toward hydrophobic substrates .…”
mentioning
confidence: 99%
“…Recently, many studies have successfully demonstrated that the hydrophobic modification on supports helps to enhance the catalysis of supported metal nanoparticles. The hydrophobic mesoporous polymeric shell endowed the Au@polymer nanostructure with the selective catalytic activity by selectively allowing hydrophobic molecules to pass through the shell to reach the catalytic Au sites . Superhydrophobic SBA-15-supported Au nanoparticles using surface passivation displayed much improved catalytic activity and selectivity toward hydrophobic substrates . In the catalytic hydrogenation of aromatic ketones by Pd/SiO 2 , the silylation of the SiO 2 support improved the selectivity by weakening the interaction of alcohols on Pd and thus suppressing their consecutive reduction .…”
mentioning
confidence: 99%